WORKPLACE STRESS AMONG PERSONNEL OF PUBLISHING COMPANY, COPING AND WORKING ABILITY - Blumberga, Solveiga; Mangule, Raimonda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Most of the life of a human is spent at work, creating the economic and material foundation of the society, which, to a large extent, depends on the working ability of these people. The printing and publishing company is experiencing an increase in the numbers of days spent off work due to sickness, overtime hours and on-job casualties. The aim of the research is to study the causes of workplace stress among the personnel, the coping strategies, the working abilities and their mutual relationship. The research questions are: What are the major causes of workplace stress, what coping strategies are used by the personnel, what is the level of the working ability among the personnel, and are there statistically significant correlations between workplace stress, coping strategies and working ability?Based on the results, it was found that the key causes of workplace stress include the high volumes and amount of work. Active coping strategies are used most frequently to handle stress. No respondents were found to have low levels of working ability, A statistically significant correlation was found between the ratings on the scales “organisational culture” and “working ability”, i.e., the lower the evaluation of the organisation among the personnel, the lower the working ability. An explanation for this fact might be the different values of the personnel and the organisation.